Answer:
The function is increasing from x = 0 to x = 1.
Step-by-step explanation:
The value of g(0) is less than g(1), meaning g(x) increased from x=0 to x=1.
Answer with Step-by-step explanation:
Let a mass weighing 16 pounds stretches a spring
feet.
Mass=![m=\frac{W}{g}](https://tex.z-dn.net/?f=m%3D%5Cfrac%7BW%7D%7Bg%7D)
Mass=![m=\frac{16}{32}](https://tex.z-dn.net/?f=m%3D%5Cfrac%7B16%7D%7B32%7D)
![g=32 ft/s^2](https://tex.z-dn.net/?f=g%3D32%20ft%2Fs%5E2)
Mass,m=
Slug
By hook's law
![w=kx](https://tex.z-dn.net/?f=w%3Dkx)
![16=\frac{8}{3} k](https://tex.z-dn.net/?f=16%3D%5Cfrac%7B8%7D%7B3%7D%20k)
![k=\frac{16\times 3}{8}=6 lb/ft](https://tex.z-dn.net/?f=k%3D%5Cfrac%7B16%5Ctimes%203%7D%7B8%7D%3D6%20lb%2Fft)
![f(t)=10cos(3t)](https://tex.z-dn.net/?f=f%28t%29%3D10cos%283t%29)
A damping force is numerically equal to 1/2 the instantaneous velocity
![\beta=\frac{1}{2}](https://tex.z-dn.net/?f=%5Cbeta%3D%5Cfrac%7B1%7D%7B2%7D)
Equation of motion :
![m\frac{d^2x}{dt^2}=-kx-\beta \frac{dx}{dt}+f(t)](https://tex.z-dn.net/?f=m%5Cfrac%7Bd%5E2x%7D%7Bdt%5E2%7D%3D-kx-%5Cbeta%20%5Cfrac%7Bdx%7D%7Bdt%7D%2Bf%28t%29)
Using this equation
![\frac{1}{2}\frac{d^2x}{dt^2}=-6x-\frac{1}{2}\frac{dx}{dt}+10cos(3t)](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7D%5Cfrac%7Bd%5E2x%7D%7Bdt%5E2%7D%3D-6x-%5Cfrac%7B1%7D%7B2%7D%5Cfrac%7Bdx%7D%7Bdt%7D%2B10cos%283t%29)
![\frac{1}{2}\frac{d^2x}{dt^2}+\frac{1}{2}\frac{dx}{dt}+6x=10cos(3t)](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7D%5Cfrac%7Bd%5E2x%7D%7Bdt%5E2%7D%2B%5Cfrac%7B1%7D%7B2%7D%5Cfrac%7Bdx%7D%7Bdt%7D%2B6x%3D10cos%283t%29)
![\frac{d^2x}{dt^2}+\frac{dx}{dt}+12x=20cos(3t)](https://tex.z-dn.net/?f=%5Cfrac%7Bd%5E2x%7D%7Bdt%5E2%7D%2B%5Cfrac%7Bdx%7D%7Bdt%7D%2B12x%3D20cos%283t%29)
Auxillary equation
![m^2+m+12=0](https://tex.z-dn.net/?f=m%5E2%2Bm%2B12%3D0)
![m=\frac{-1\pm\sqrt{1-4(1)(12)}}{2}](https://tex.z-dn.net/?f=m%3D%5Cfrac%7B-1%5Cpm%5Csqrt%7B1-4%281%29%2812%29%7D%7D%7B2%7D)
![m=\frac{-1\pmi\sqrt{47}}{2}](https://tex.z-dn.net/?f=m%3D%5Cfrac%7B-1%5Cpmi%5Csqrt%7B47%7D%7D%7B2%7D)
![m_1=\frac{-1+i\sqrt{47}}{2}](https://tex.z-dn.net/?f=m_1%3D%5Cfrac%7B-1%2Bi%5Csqrt%7B47%7D%7D%7B2%7D)
![m_2=\frac{-1-i\sqrt{47}}{2}](https://tex.z-dn.net/?f=m_2%3D%5Cfrac%7B-1-i%5Csqrt%7B47%7D%7D%7B2%7D)
Complementary function
![e^{\frac{-t}{2}}(c_1cos\frac{\sqrt{47}}{2}+c_2sin\frac{\sqrt{47}}{2})](https://tex.z-dn.net/?f=e%5E%7B%5Cfrac%7B-t%7D%7B2%7D%7D%28c_1cos%5Cfrac%7B%5Csqrt%7B47%7D%7D%7B2%7D%2Bc_2sin%5Cfrac%7B%5Csqrt%7B47%7D%7D%7B2%7D%29)
To find the particular solution using undetermined coefficient method
![x_p(t)=Acos(3t)+Bsin(3t)](https://tex.z-dn.net/?f=x_p%28t%29%3DAcos%283t%29%2BBsin%283t%29)
![x'_p(t)=-3Asin(3t)+3Bcos(3t)](https://tex.z-dn.net/?f=x%27_p%28t%29%3D-3Asin%283t%29%2B3Bcos%283t%29)
![x''_p(t)=-9Acos(3t)-9sin(3t)](https://tex.z-dn.net/?f=x%27%27_p%28t%29%3D-9Acos%283t%29-9sin%283t%29)
This solution satisfied the equation therefore, substitute the values in the differential equation
![-9Acos(3t)-9Bsin(3t)-3Asin(3t)+3Bcos(3t)+12(Acos(3t)+Bsin(3t))=20cos(3t)](https://tex.z-dn.net/?f=-9Acos%283t%29-9Bsin%283t%29-3Asin%283t%29%2B3Bcos%283t%29%2B12%28Acos%283t%29%2BBsin%283t%29%29%3D20cos%283t%29)
![(3B+3A)cos(3t)+(3B-3A)sin(3t)=20cso(3t)](https://tex.z-dn.net/?f=%283B%2B3A%29cos%283t%29%2B%283B-3A%29sin%283t%29%3D20cso%283t%29)
Comparing on both sides
![3B+3A=20](https://tex.z-dn.net/?f=3B%2B3A%3D20)
![3B-3A=0](https://tex.z-dn.net/?f=3B-3A%3D0)
Adding both equation then, we get
![6B=20](https://tex.z-dn.net/?f=6B%3D20)
![B=\frac{20}{6}=\frac{10}{3}](https://tex.z-dn.net/?f=B%3D%5Cfrac%7B20%7D%7B6%7D%3D%5Cfrac%7B10%7D%7B3%7D)
Substitute the value of B in any equation
![3A+10=20](https://tex.z-dn.net/?f=3A%2B10%3D20)
![3A=20-10=10](https://tex.z-dn.net/?f=3A%3D20-10%3D10)
![A=\frac{10}{3}](https://tex.z-dn.net/?f=A%3D%5Cfrac%7B10%7D%7B3%7D)
Particular solution, ![x_p(t)=\frac{10}{3}cos(3t)+\frac{10}{3}sin(3t)](https://tex.z-dn.net/?f=x_p%28t%29%3D%5Cfrac%7B10%7D%7B3%7Dcos%283t%29%2B%5Cfrac%7B10%7D%7B3%7Dsin%283t%29)
Now, the general solution
![x(t)=e^{-\frac{t}{2}}(c_1cos(\frac{\sqrt{47}t}{2})+c_2sin(\frac{\sqrt{47}t}{2})+\frac{10}{3}cos(3t)+\frac{10}{3}sin(3t)](https://tex.z-dn.net/?f=x%28t%29%3De%5E%7B-%5Cfrac%7Bt%7D%7B2%7D%7D%28c_1cos%28%5Cfrac%7B%5Csqrt%7B47%7Dt%7D%7B2%7D%29%2Bc_2sin%28%5Cfrac%7B%5Csqrt%7B47%7Dt%7D%7B2%7D%29%2B%5Cfrac%7B10%7D%7B3%7Dcos%283t%29%2B%5Cfrac%7B10%7D%7B3%7Dsin%283t%29)
From initial condition
x(0)=2 ft
x'(0)=0
Substitute the values t=0 and x(0)=2
![2=c_1+\frac{10}{3}](https://tex.z-dn.net/?f=2%3Dc_1%2B%5Cfrac%7B10%7D%7B3%7D)
![2-\frac{10}{3}=c_1](https://tex.z-dn.net/?f=2-%5Cfrac%7B10%7D%7B3%7D%3Dc_1)
![c_1=\frac{-4}{3}](https://tex.z-dn.net/?f=c_1%3D%5Cfrac%7B-4%7D%7B3%7D)
![x'(t)=-\frac{1}{2}e^{-\frac{t}{2}}(c_1cos(\frac{\sqrt{47}t}{2})+c_2sin(\frac{\sqrt{47}t}{2})+e^{-\frac{t}{2}}(-c_1\frac{\sqrt{47}}{2}sin(\frac{\sqrt{47}t}{2})+\frac{\sqrt{47}}{2}c_2cos(\frac{\sqrt{47}t}{2})-10sin(3t)+10cos(3t)](https://tex.z-dn.net/?f=x%27%28t%29%3D-%5Cfrac%7B1%7D%7B2%7De%5E%7B-%5Cfrac%7Bt%7D%7B2%7D%7D%28c_1cos%28%5Cfrac%7B%5Csqrt%7B47%7Dt%7D%7B2%7D%29%2Bc_2sin%28%5Cfrac%7B%5Csqrt%7B47%7Dt%7D%7B2%7D%29%2Be%5E%7B-%5Cfrac%7Bt%7D%7B2%7D%7D%28-c_1%5Cfrac%7B%5Csqrt%7B47%7D%7D%7B2%7Dsin%28%5Cfrac%7B%5Csqrt%7B47%7Dt%7D%7B2%7D%29%2B%5Cfrac%7B%5Csqrt%7B47%7D%7D%7B2%7Dc_2cos%28%5Cfrac%7B%5Csqrt%7B47%7Dt%7D%7B2%7D%29-10sin%283t%29%2B10cos%283t%29)
Substitute x'(0)=0
![0=-\frac{1}{2}\times c_1+10+\frac{\sqrt{47}}{2}c_2](https://tex.z-dn.net/?f=0%3D-%5Cfrac%7B1%7D%7B2%7D%5Ctimes%20c_1%2B10%2B%5Cfrac%7B%5Csqrt%7B47%7D%7D%7B2%7Dc_2)
![\frac{\sqrt{47}}{2}c_2-\frac{1}{2}\times \frac{-4}{3}+10=0](https://tex.z-dn.net/?f=%5Cfrac%7B%5Csqrt%7B47%7D%7D%7B2%7Dc_2-%5Cfrac%7B1%7D%7B2%7D%5Ctimes%20%5Cfrac%7B-4%7D%7B3%7D%2B10%3D0)
![\frac{\sqrt{47}}{2}c_2=-\frac{2}{3}-10=-\frac{32}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B%5Csqrt%7B47%7D%7D%7B2%7Dc_2%3D-%5Cfrac%7B2%7D%7B3%7D-10%3D-%5Cfrac%7B32%7D%7B3%7D)
![c_2==-\frac{64}{3\sqrt{47}}](https://tex.z-dn.net/?f=c_2%3D%3D-%5Cfrac%7B64%7D%7B3%5Csqrt%7B47%7D%7D)
Substitute the values then we get
![x(t)=e^{-\frac{t}{2}}(-\frac{4}{3}cos(\frac{\sqrt{47}t}{2})-\frac{64}{3\sqrt{47}}sin(\frac{\sqrt{47}t}{2})+\frac{10}{3}cos(3t)+\frac{10}{3}sin(3t)](https://tex.z-dn.net/?f=x%28t%29%3De%5E%7B-%5Cfrac%7Bt%7D%7B2%7D%7D%28-%5Cfrac%7B4%7D%7B3%7Dcos%28%5Cfrac%7B%5Csqrt%7B47%7Dt%7D%7B2%7D%29-%5Cfrac%7B64%7D%7B3%5Csqrt%7B47%7D%7Dsin%28%5Cfrac%7B%5Csqrt%7B47%7Dt%7D%7B2%7D%29%2B%5Cfrac%7B10%7D%7B3%7Dcos%283t%29%2B%5Cfrac%7B10%7D%7B3%7Dsin%283t%29)
Answer:
Step-by-step explanation:
is it 34 because you haven't moved the bodies. however including you there's 35???
Answer:
9/4 * 3/4 = 27/16 = 1 ![\frac{9}{16}](https://tex.z-dn.net/?f=%5Cfrac%7B9%7D%7B16%7D)
Step-by-step explanation: